Low tumor interleukin-1β expression predicts a limited effect of adjuvant platinum-based chemotherapy for patients with completely resected lung adenocarcinoma: an identification and validation study - Safi, Seyer; Krzykalla, Julia; Hoffmann, Hans; Benner, Axel; Bischoff, Helge; Eichhorn, Martin E.; Kriegsmann, Mark; Poschke, Isabel; Stögbauer, Fabian; Umansky, Ludmila; Mogler, Carolin; Weichert, Wilko; et al. (Pulmonology, 2024)
Adjuvant platinum-based chemotherapy for completely resected non-small cell lung cancer is associated with modest improvement in survival; nevertheless, no validated biomarker exists for predicting the benefit or harm of adjuvant platinum-based chemotherapy. We simultaneously measured 27 cytokines in operative tumor specimens from a discovery cohort (n = 97) by multiplex immunoassay; half of the patients received adjuvant platinum-based chemotherapy, and the other half were observed. We tested possible prognostic and predictive factors in multivariate Cox models for overall survival (OS) and relapse-free survival (RFS), and a tree-based method was applied to detect predictive factors with respect to RFS. The results were validated in an independent validation cohort (n = 93). Fifty-two of 97 (54 %) patients in the discovery cohort and 50 of 93 (54 %) in the validation cohort received adjuvant chemotherapy; forty-four (85 %) patients in the discovery cohort and 37 (74 %) in the validation cohort received four cycles as planned. In patients with low IL-1β-expressing tumors, RFS and OS were worse after adjuvant chemotherapy than after observation. The limited effect of adjuvant chemotherapy for patients with low IL-1β-expressing tumors was confirmed in the validation cohort. Additionally, RFS and OS were prolonged by adjuvant chemotherapy only in patients with high IL-1β-expressing tumors in the validation cohort. This study identified and validated low tumor IL-1β expression as a potential biomarker of a limited response to adjuvant platinum-based chemotherapy after complete resection of pulmonary adenocarcinoma. This finding has the potential to inform adjuvant treatment decisions.
Gesehen am 06.08.2025